Students’ Perceptions of Online Learning in Writing Descriptive Text on Students of the Faculty of Economics and Business, Mahendradatta University - I Nyoman Bawa Bagiada; Ni Putu Andini Desiyanti Laksmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2024)
The purpose of this study was to determine the students' perceptions of online learning in writing descriptive text, which included recognize, make stimuli, experiences, knowledge, motivation, social interaction, understanding, acceptance, responses, and future solutions regarding online learning itself in on students of the Faculty of Economics and Business, Mahendradatta University for third semester, which was done by the english lecturer. In this study, a descriptive qualitative research design was used. An english teacher and 45 students who had completed online learning participated in this study. The teacher's utterances and questionnaire answer sheets were used as data sources in this study. The data was gathered through interviews with the teacher and the distribution of a Google Form questionnaire to the online learning students. According to the findings of the interview, perception related to the teacher explains english material well through online learning with a percentage of 62,9%. It can be concluded that students' perceptions of online English learning during the Covid-19 pandemic are positive and can be effectively implemented.